2014
DOI: 10.1353/jda.2014.0073
|View full text |Cite
|
Sign up to set email alerts
|

Financial Intermediation and Stock Market Volatility in a Small Bank-Dominated Economy

Abstract: In many small developing countries, the benefits of capital market development are not realized, as banks dominate and stock markets struggle to establish a firm footing in the economy, remaining relatively illiquid and volatile. This paper examines the determinants of stock market volatility in such conditions, specifically investigating the role that banks play in engendering volatility. Although significant amounts of research have been conducted on the determinants of stock market volatility in large devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The process also produces many uncertain factors which affect bank risk, and bank risk breeds potential crises. Therefore, regulatory authorities should also be vigilant about the transmission of adverse effects of financial market development to financial intermediaries, including banks (Noman et al, 2018;Tennant and Tracey, 2014).…”
Section: Subregional Discussionmentioning
confidence: 99%
“…The process also produces many uncertain factors which affect bank risk, and bank risk breeds potential crises. Therefore, regulatory authorities should also be vigilant about the transmission of adverse effects of financial market development to financial intermediaries, including banks (Noman et al, 2018;Tennant and Tracey, 2014).…”
Section: Subregional Discussionmentioning
confidence: 99%
“…Brumm, Kubler, Grill and Schmedders (2014) showed that margin regulation in the aggregate economy has a depressing effect on the volatility of asset returns. Tennant and Tracey (2014) investigated the link between bank and stock market volatility in small but bank overshadowed country, using generalized autoregressive model, and found that strict regulations determine market volatility. Bleich, Fendel and Bulke (2013) studied the effect of interest rate on financial market stress proxy by market volatility.…”
Section: Theoretical Foundation For the Studymentioning
confidence: 99%
“…The result revealed that KLCI, GDP and INT have positive and significant influence on bank loans but there is no counter reaction from bank loans. In relation to the foregoing is that, Tennant & Tracey (2014) had examined how banks core functions impact stock market fluctuation in Jamaica using an unconditional descriptive measure of realized volatility and Generalized Autoregressive Conditional Heteroskedasticity (GARCH) specification on quarterly data. Such data include deposit to asset, loan to asset, ratio of credit to private sector to loans, spread, liquid asset ratio in a simple autoregression with exogenous variables (ARX).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The financial crisis resuscitated studies on several issues such as banks shock transmission, financial pollution, stock return estimation and market efficiency hypotheses. Though, some studies focused on these issues (Adrian and Shin, 2010;Karkowska, 2013;Tennant and Tracey, 2014); an aspect which has received less attention is study on the influence of financial intermediation on stock price of Deposit Money Banks (DMBs) in Nigeria. This aspect is important due to the need to have an informed understanding of the banking sector features, its reflection and transmission to stock prices as well as shocks dissemination process in the economy.…”
Section: Introductionmentioning
confidence: 99%